The Effect of Non Performing Financing (NPF) and Operating Expenses of Operating Income (BOPO) on Return on Equity (ROE) on PT. Bank Bri Syariah, Tbk. - nofriyanti nofriyanti; kamaluddin ritonga; sry lestari; damri batubara (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The background of this research is the incompatibility of theory with facts. Based on financial report data obtained from PT. Bank BRI Syria, Tbk. The period 2011-2019 tends to fluctuate. Financial ratios that can affect the rise and fall of the Return On Equity variable in this study are seen from the increase and decrease in the Non-Performing Financing variable and the Operating Income Operating Cost variable. The formulation of the problem in this study is whether there is an effect of Non-Performing Financing and Operational Costs of Operating Income on Return On Equity at PT. Bank BRI Syariah, Tbk. 2011-2019 period. This study aims to determine the effect of Non-Performing Financing and Operational Cost of Operating Income on Return On Equity at PT. Bank BRI Syariah, Tbk. Period 2011-2019 partially and simultaneously. This study discusses the financial statements related to the theory of the Non-Performing Financing variable and the Operating Cost of Operational Income variable on the Return On Equity variable. And related to other fields of Islamic banking science. This type of research is quantitative research, the data source used is secondary data through www. BRI Syariah.co.id. The sample of this research is 36 with data analysis used is multiple linear regression, by performing descriptive statistical tests, normality tests, linearity tests, classical assumption tests, hypothesis tests, R2 determination coefficient tests, and F tests, and the data is processed with the help of Software Eviews. Based on the results of the research partially Non-Performing Financing variables have a significant effect on Return On Equity, this is evidenced by the t-test analysis. And on the variable Operating Costs, Operating Income partially has a significant effect on Return On Equity, this is evidenced by the t-test analysis. Then simultaneously the variables of Non-Performing Financing and Operating Costs of Operating Income have a joint effect on Return On Equity